Glazing-related problems due to high temperatures in double skin façades - Duarte, Rogério (2013)
The thermal behaviour of a double skin façade building is modelled using the DOE-2 building energy simulation program. Maximum temperatures of glazed components of the double skin façade are determined to assess the occurrence of glazing-related problems, such as reduced thermal and aesthetic performance, increased maintenance costs and even injury hazards. The importance of detailed thermal modelling of double skin façades and of its glazed componentes is concluded.